1998
DOI: 10.1177/096368979800700410
|View full text |Cite
|
Sign up to set email alerts
|

Complement Permeability in Bio-Artificial Endocrine Pancreas Using a Diffusion Chamber

Abstract: Immunoisolation is a potentially important approach to transplanting islets without any immunosuppressive therapy. This study was designed to investigate whether complement penetrates into the diffusion chamber that we developed for a bioartificial endocrine pancreas (Bio-AEP). The results showed that within 12-24 h, when a Nuclepore membrane (Nuclepore Corp., California) was the sole barrier, complement permeated 100%. However, the Nuclepore membrane used together with a mixed matrix prevented complement pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In this study, it was possible to transplant mouse b cells into rats using Bio-AEP. This result was in agreement with those reported in previous studies [7,8]. Edamura et al (2004) reported pancreatectomized dogs could be transplanted with porcine pancreatic endocrine cells in a Bio-AEP [3].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In this study, it was possible to transplant mouse b cells into rats using Bio-AEP. This result was in agreement with those reported in previous studies [7,8]. Edamura et al (2004) reported pancreatectomized dogs could be transplanted with porcine pancreatic endocrine cells in a Bio-AEP [3].…”
supporting
confidence: 93%
“…We became interested in these reports on the Bio-AEP, since we thought it might improve -Note-sexual dysfunction induced by neuroendocrine dysfunction [11,13,19,21] based on hyperglycemia and insulin insufficiency. In addition, the Bio-AEP may make possible transplantation of b cells from different species because the Bio-AEP shows promise for long-term xenotransplantation without immunosuppression [7,8]. Therefore, the object of our study was to confirm whether or not mouse b cells could improve hyperglycemia and sexual dysfunction caused by diabetes mellitus.…”
mentioning
confidence: 99%
“…[21] The complex 3D structure of the hydrogel can slow the permeation of complement components enough to hamper cytolytic capabilities. [235] Schneider et al utilized alginate-based microencapsulation of pancreatic islets to extend xenogeneic islet grafts from 4-8 days for nonencapsulated islets to >7 months for encapsulated islets. Encapsulated cells that were retrieved 10 and 36 weeks post-transplantation exhibited >85% viability with minor cellular reactions along the alginate surface, suggesting the root cause for a reduction in glucose clearance rate was pore nutrient and oxygen supply rather than complementdependent responses.…”
Section: Tuning Microgel Composition For Improved Protection and Usability Of Cellular Cargomentioning
confidence: 99%
“…This membrane also permits the permeation of complement C3 (molecular weight of 195 kD). Interestingly, if the chamber was loaded with the mixed matrix containing complement C3, only 20% of the C3 diffused through the 0.2‐μm membrane in a 24‐h period (vs 78% without matrix) 24. The effect of membrane pore size on the entry of complement into the chamber was also tested, in vitro, by immersing chambers constructed of a membrane with a 0.1‐μm or 0.2‐μm pore size, in medium containing fresh human serum.…”
Section: Immunoisolation Devicesmentioning
confidence: 99%
“…Based on the amount of hemoglobin released from lysed erythrocytes into the incubation medium, chambers made from smaller pore size membranes allowed less lysis, suggesting that the pore size was also instrumental in reducing complement diffusion into the chamber. When the chambers were immersed in medium containing 10% human serum for 4 weeks, the diameter of 0.1‐μm pores was reduced by 25% and that of 0.2‐μm pores by 34% 24…”
Section: Immunoisolation Devicesmentioning
confidence: 99%